CHALLENGES ENCOUNTERED BY SECOND-YEAR STUDENTS IN THE DOCUMENTARY PROJECT AT UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES = NHỮNG KHÓ KHĂN CỦA SINH VIÊN NĂM THỨ HAI TRƯỜNG ĐẠI HỌC NGOẠI NGỮ KHI THỰC HIỆN DỰ ÁN DOCUMENTARY - Nguyễn, Bích Ngọc (2020)
Challenges that students encountered in project-based learning has been mentioned by a number of researchers in their implementation studies (Krajcik et al., 1998; Stauffacher et al., 2006; Harmer and Stokes, 2014). Nevertheless, there is limited empirical research directly addressing this matter in English language teaching (Harmer and Stokes, 2014). The shortage of evidence on the challenges that students encounter in project-based learning leaves a gap that needs to be filled. Focusing on the context of the Faculty of English Language Teacher Education, University of Languages and International Studies (FELTE, ULIS), this paper attempts to investigate the challenges that students faced, their responses to the challenges and some suggestions they made for further improvement in a project called the Documentary project.